Case Report: A rare case of sintilimab-induced dermatomyositis in a patient with gastric cancer - Mou, Peipei; Li, Fanghua; Wang, Yingying; Zhao, Feifei (Frontiers in Oncology, 2025)
The PD-1 inhibitor sintilimab has been approved for the treatment of various malignancies. Here, we reported a rare case of sintilimab-induced dermatomyositis in a patient with gastric cancer and liver metastasis to raise awareness of this serious adverse event. A 64-year-old man presented with the onset of gastric cancer and liver metastasis and received two cycles of sintilimab plus nab-paclitaxel. The patient experienced fever, thrombocytopenia, and rash during the first-cycle treatment, followed by bilateral ptosis, dysphagia, slurred speech, and myalgia during the second-cycle treatment. Elevated muscle enzymes, electromyography, and positive myositis antibodies confirmed the diagnosis of dermatomyositis. He was treated with high-dose corticosteroids and immunoglobulin, resulting in symptom improvement. This case widens the spectrum of immune-related toxicity associated with sintilimab, as well as highlights the need for early recognition and management of these events in patients receiving ICIs.